SUSTAINABLE UTILIZATION OF WATER HYACINTH AS SRF RAW MATERIAL IN MICRO, SMALL, AND MEDIUM ENTERPRISES SCALE - Gabriela Kristanti, Maria
In order to support government programs in increasing the EBT mix target in 2025 it reaches 23% with details of 13-15% coming from PLT EBT, 2-5% coming from PLT Bioenergy, and 2-3% coming from Biofuels, biomass utilization from all improved sector. One of the biomass with low utilization is water hyacinth (Eicohornia crassipas). Water hyacinth is an aquatic weed that has a high growth rate and is difficult to control. The existence of water hyacinths is a problem in various sectors of living things such as the environment, transportation, economy, tourism, health, and others. On the other hand, water hyacinth has the potential to be used to produce economically valuable products. In general, water hyacinth can be used as a handicraft material, animal feed, and as a phytoremediation plant. The use of water hyacinth as fuel has also been successfully implemented, such as biogas, bioethanol, and briquettes or pellets. In the West Java reservoir, the high amount of water hyacinth also has a high potential for utilization. In the Saguling Reservoir, water hyacinth is utilized by the Biomass Operation System of Saguling (BOSS) for the production solid recovered fuel (SRF) for co-firing at Pelabuhan Ratu Power Plant and Lontar Power Plant. However, the production process does not run optimally due to the drying process which is very dependent on the weather and the tough nature of water hyacinth, making it difficult to enumerate. As a result, the production process is hampered and production capacity is low, only 0.3 tons/day. Production unit development was carried out to optimize the SRF production process in the BOSS unit. Simple drying system design with sun drying method and biodrying method to reduce the use of drying area and not depend on the weather carried out in an open laboratory. Production system design and development of SRF production units were also carried out on the MSME scale based on the availability of water hyacinth in the Saguling, Cirata, and Jatiluhur Reservoirs. Sun drying in the BOSS unit can reduce water hyacinth water content up to 60% of the initial moisture content. Production of SRF in the BOSS unit could not be carried out optimally due to two problem factors, namely the drying system which is very dependent on the weather and requires large areas of land, and the clayey nature of water hyacinth which complicates the chopping operation. The water hyacinth drying experiment reduced water content until 32% with bamboo cage method, 57% with bamboo racked bamboo mehtod, and 16-40% dengan “keranda” method. Biodrying without pre-drying is not suitable for fresh water hyacinth with a moisture content of more than 90% because it causes the sample to rot but there is a mass loss of 15.9-30%. The water hyacinth samples around the BOSS unit have the ultimate composition (air-dried basis) 22.67-35.12% C, 4.37-5.64% H, 28.06-45.36% O, 1.05-1.15% N, and 0.13-0.46% S as well as the proximate composition (air dried basis) 12.60-43.49% ash, 46.67-59.76% volatile matter, and 0.57-14.86% fixed carbon. The HHV values of water hyacinth, wood, and SRF samples around the BOSS unit were 8.41-15.65 MJ/kg, 18.16-18.35 MJ/kg, and 13.09-15.12 MJ/kg respectively. The availability of water hyacinth in the Saguling Reservoir, Cirata Reservoir, and Jatiluhur Reservoir cannot meet the daily needs of SRF co-firing PLTU Pelabuhan Ratu and PLTU Lontar can supply lower quantities. Based on the scenario for the establishment of MSME units, 1-15 MSME units can be established in the Saguling Reservoir, 33-440 MSME units in the Cirata Reservoir, and 9-1,217 MSME units in the Jatiluhur Reservoir to produce SRF at a harvesting capacity of 9.5 Ha, 285.00 Ha, and 788.50 Ha. The SRF products produced by BOSS meet the class-2 and class-3 standards of SNI 8966:2021 and class-4 European Standardization. The higher the number of workers, the lower the profit earned by the BOSS unit so that adjustments to the minimum production capacity are needed based on the number of workers. The economic analysis model with the lowest number of workers at the highest production capacity and receiving grants and subsidies from the Government will generate the highest profit. The economic analysis model with the highest number of workers at the lowest production capacity with a scenario without grants and subsidies from the Government will produce the lowest profit.